1992
DOI: 10.1128/jb.174.9.3011-3020.1992
|View full text |Cite
|
Sign up to set email alerts
|

The lemA gene required for pathogenicity of Pseudomonas syringae pv. syringae on bean is a member of a family of two-component regulators

Abstract: The lemA gene of the plant pathogen Pseudomonas syringae pv. syringae is required for disease lesion formation on bean plants. Cosmid clones that complemented a lemA mutant in trans were isolated previously. The lemA gene was localized by subcloning and transposon mutagenesis. The lemA region and flanking DNA were sequenced, and an open reading frame of 2.7 kb was identified. The nucleotide and predicted amino acid sequences of the kmA gene showed sequence similarity to a family of prokaryotic two-component re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(139 citation statements)
references
References 48 publications
5
134
0
Order By: Relevance
“…In addition, surface motility could be restored in the gacS mutant upon introduction of pEMH97 encoding the heterologous wild-type gacS gene from Pseudomonas syringae pv. syringae (Hrabak & Willis, 1992), supporting the finding of Koch et al (2002) that amphisin synthesis is regulated by gacS (compare Fig.1C and D). and solidified with 0?6 % agar.…”
Section: Surface Motility Of Strain Dss73supporting
confidence: 76%
“…In addition, surface motility could be restored in the gacS mutant upon introduction of pEMH97 encoding the heterologous wild-type gacS gene from Pseudomonas syringae pv. syringae (Hrabak & Willis, 1992), supporting the finding of Koch et al (2002) that amphisin synthesis is regulated by gacS (compare Fig.1C and D). and solidified with 0?6 % agar.…”
Section: Surface Motility Of Strain Dss73supporting
confidence: 76%
“…We found that despite its relatively small genome, TM7x contains many pathogenesis-related virulence gene homologs, including two virulence islands encoding separate type IV secretion systems and membrane-associated virulence-related proteins, such as OmpA (36) and LemA (37), as well as cholinebinding proteins (38) (Table S2). It is particularly interesting to point out that the TM7x genome contains various ORFs encoding predicted proteins with toxin-antitoxin (TA) domains, such as VapC, VapB, and xenobiotic response element (39), as well as an abortive infection protein homolog known to promote cell death and limit phage replication within a bacterial population (40).…”
Section: Conserved Gene Synteny But Further Genome Reduction Is Evidementioning
confidence: 99%
“…GacA is part of a two-component system and belongs to the FixJ family of response regulators (Laville et al, 1992). The cognate sensor appears to be the transmembrane protein LemA (Hrabak and Willis, 1992;Rich et al, 1994). Both the gacA and lemA genes are highly conserved in fluorescent pseudomonads (Liao et al, 1994;Corbell and Loper, 1995;Grewal et al, 1995).…”
Section: Introductionmentioning
confidence: 99%